(untitled) (Journal of Environmental Science and Natural Resources, 2019)
The study has been carried out in a Riverine Island of the Ganges River in Chapai Nawabganj District of Bangladesh to evaluate the livelihood status and the association between different livelihood capitals and well-being status. Both qualitative and quantitative data are collected through household questionnaire survey and field observation. Most of the surveyed households are found either poor or hard core poor. This study identified five capitals of livelihood i.e. human, social, natural, financial and physical capitals with specific indicators. Family size and education indicators of human capital, organizational attachment of social capital, total and operational land of natural capital, value of livestock, size of savings and loan of financial capital and mobile phone of physical capital are statistically significant with the well-being status. This means higher value of indicators indicate higher the well-being status. Hence, this study assumes that most of the char dwellers are poor or hard core poor because their livelihood capitals and assets are not in satisfactory level. This study suggests providing necessary institutional and organizational supports for strengthening the livelihood of char dwellers. J. Environ. Sci. & Natural Resources, 11(1-2): 27-36 2018